2000
DOI: 10.1021/bi0005815
|View full text |Cite
|
Sign up to set email alerts
|

Catalase-Peroxidase (Mycobacterium tuberculosis KatG) Catalysis and Isoniazid Activation

Abstract: Resonance Raman spectra of native, overexpressed M. tuberculosis catalase-peroxidase (KatG), the enzyme responsible for activation of the antituberculosis antibiotic isoniazid (isonicotinic acid hydrazide), have confirmed that the heme iron in the resting (ferric) enzyme is high-spin five-coordinate. Difference Raman spectra did not reveal a change in coordination number upon binding of isoniazid to KatG. Stopped-flow spectrophotometric studies of the reaction of KatG with stoichiometric equivalents or small e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
158
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(178 citation statements)
references
References 58 publications
18
158
1
Order By: Relevance
“…Studies have shown that Compound II can be stably generated in the reaction of HRP Compound I with INH, further supporting the operation of a classic peroxidatic mechanism of INH oxidation for this enzyme (19). The same authors also identified Compound I in the reaction of M. tuberculosis CP with INH and speculated that a similar peroxidatic pathway may be utilized (19). Based upon these data and the amenability of HRP to characterization of enzymearomatic compound complexes using NMR methods (20 -28), we have, therefore, undertaken a high resolution NMR characterization of the interactions between horseradish peroxidase C (HRPC) and INH.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Studies have shown that Compound II can be stably generated in the reaction of HRP Compound I with INH, further supporting the operation of a classic peroxidatic mechanism of INH oxidation for this enzyme (19). The same authors also identified Compound I in the reaction of M. tuberculosis CP with INH and speculated that a similar peroxidatic pathway may be utilized (19). Based upon these data and the amenability of HRP to characterization of enzymearomatic compound complexes using NMR methods (20 -28), we have, therefore, undertaken a high resolution NMR characterization of the interactions between horseradish peroxidase C (HRPC) and INH.…”
mentioning
confidence: 66%
“…Later work from the same group demonstrated similar activity using partially purified M. tuberculosis CP (6). Studies have shown that Compound II can be stably generated in the reaction of HRP Compound I with INH, further supporting the operation of a classic peroxidatic mechanism of INH oxidation for this enzyme (19). The same authors also identified Compound I in the reaction of M. tuberculosis CP with INH and speculated that a similar peroxidatic pathway may be utilized (19).…”
mentioning
confidence: 82%
“…Frozen sample powders were packed into precision-bore quartz EPR tubes immersed in an isopentane bath and were examined using a Varian EPR spectrometer operating at X-band. A finger Dewar inserted into the EPR cavity was used for recording spectra at liquid nitrogen (77 K) temperature, while a liquid helium cryostat and Heli-Tran liquid helium transfer system (Advanced Research Systems, Inc., Allentown, PA) were used for EPR at 5.5 K. EPR data acquisition and manipulation was made using WinEPR software (14). Simulation of EPR spectra was performed using software provided by F. Neese (22,23).…”
Section: Materials-escherichia Colimentioning
confidence: 99%
“…Optical stopped-flow experiments have shown that Mycobacterium tuberculosis KatG, like other peroxidases, forms the oxyferryl iron porphyrin -cation radical known as Compound I (Cmpd I) when the resting (ferric) enzyme is treated with alkyl hydroperoxides (14). Catalase-peroxidases from other organisms behave similarly (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation